Penerapan Pendidikan Karakter Melalui Pembelajaran Seni Musik - Suhirno Suhirno; Hesti Yunitiara Rizqi (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Students who are intelligent and have good character start from the educational process carried out at school. Character education is very important to shape the personality of students so that they have good character in their lives. Character education is integrated in all subjects, especially in music art subjects. Students are expected to have a strong character through music art learning media. The problem in this study is how to implement character education through music art learning. The purpose of this study is to describe the implementation of character education through music art learning. The benefits of this research consist of theoretical and practical benefits, especially for art education practitioners in schools. This study uses qualitative research methods. The research objective is on the implementation of character education in music art learning. The data collection technique was carried out using observation techniques, interviews and documentation studies. The data validity technique uses data triangulation. The data analysis technique uses qualitative data analysis. The result of this study is that the instillation of the values of Cultural Education and Character of the Nation developed in the learning process of music art is not carried out separately, but these values are incorporated into the learning steps. In practice, the steps to learn music arts based on national character education are contained in certain slogans embraced by the school. The suggestion in this study is that teachers or those responsible for the selection process of regional songs and national songs in music ensemble learning should pay attention to the selection of songs so that they are easier to understand and the cultivation of character education can be achieved properly.